2016
DOI: 10.1016/j.cels.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The BLUEPRINT Data Analysis Portal

Abstract: The impact of large and complex epigenomic datasets on biological insights or clinical applications is limited by the lack of accessibility by easy, intuitive, and fast tools. Here, we describe an epigenomics comparative cyber-infrastructure (EPICO), an open-access reference set of libraries to develop comparative epigenomic data portals. Using EPICO, large epigenome projects can make available their rich datasets to the community without requiring specific technical skills. As a first instance of EPICO, we im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
142
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 18 publications
0
142
0
Order By: Relevance
“…proportion of ddcfDNA can be estimated by evaluating the coverage of the Y chromosome relative 18 to the autosomal chromosomes (see Methods) 2,32 . We verified that the proportion of ddcfDNA 19 measured by sequencing of bisulfite-treated cfDNA matched the proportion of ddcfDNA measured 20 using conventional sequencing (n=36 matched samples, Spearman's rho = 0.97, p-value < 21 2.2x10 -16 , see Methods, supplemental figure 2), and then quantified the proportion of ddcfDNA 22 in urine for all sex-mismatched donor-recipient transplant pairs (n=46). We observed a very large 23 range of ddcfDNA values across all samples (3%-99%).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…proportion of ddcfDNA can be estimated by evaluating the coverage of the Y chromosome relative 18 to the autosomal chromosomes (see Methods) 2,32 . We verified that the proportion of ddcfDNA 19 measured by sequencing of bisulfite-treated cfDNA matched the proportion of ddcfDNA measured 20 using conventional sequencing (n=36 matched samples, Spearman's rho = 0.97, p-value < 21 2.2x10 -16 , see Methods, supplemental figure 2), and then quantified the proportion of ddcfDNA 22 in urine for all sex-mismatched donor-recipient transplant pairs (n=46). We observed a very large 23 range of ddcfDNA values across all samples (3%-99%).…”
mentioning
confidence: 70%
“…type specific -to determine the cell and tissue types that contribute to the mixture of host cfDNA 19 in a sample. Several recent studies have shown that profiling CpG methylation marks in urinary 20 or plasma cfDNA, via whole-genome sequencing, targeted sequencing, or PCR assays, can be 21 used to determine their tissues-of-origin and to quantify tissue-specific injury in various diseased 22 settings [7][8][9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we compiled expression quantitative trait loci (eQTL) data for protein-coding genes expressed in lung, liver, spleen and skeletal muscle from individuals with European ancestry from the GTEx Project, 67 and monocyte, T cell and neutrophil populations in individuals from BLUEPRINT. 76 We chose these tissues for potential relevance to OSA pathology: the lung is involved in OSA-related hypoxemia; 43,44 previous GWAS associations have implicated the neuromuscular junction in overnight SpO 2 levels; 22 the spleen and liver are known to mediate filtration of erythrocytes and iron homeostasis; and leukocytes are key modulators of inflammation. We calculate FDR based on JLIM p-values over the 167 comparisons shown in Table S4, where we include these eQTL analyses.…”
Section: Incorporating Gene Expression To Construct Molecular Hypothementioning
confidence: 99%
“…ENCODE (49), the Epigenome Roadmap (27), BLUEPRINT (50), and the overarching International Human Epigenome Consortium (IHEC) are dedicated to providing reference maps for key cellular states. These efforts also focus on harmonizing measurement techniques, bioinformatics standards, data models, and analytical tools for organizing, integrating, and displaying the epigenome data generated (51,52) With availability and easy use of analyses tools, it is becoming increasingly feasible for many researchers to study the epigenome in different diseases states (53). Reproducibility among laboratories is also improving, with DNA methylation profiling now benchmarked across many laboratories, and with assays potentially sufficiently robust to become applicable in clinical settings (54).…”
Section: Translational Perspectivementioning
confidence: 99%